Errors in Surgery: A Case Control Study. Issue 5 (10th November 2022) - Marsh, Katherine M.; Turrentine, Florence E.; Schenk, Worthington G.; Hanks, John B.; Schirmer, Bruce D.; Davis, John P.; McMurry, Timothy L.; Ratcliffe, Sarah J.; Zaydfudim, Victor M.; Jones, R.S.
Abstract : Objective: While errors can harm patients they remain poorly studied. This study characterized errors in the care of surgical patients and examined the association of errors with morbidity and mortality. Background: Errors have been reported to cause <10% or >60% of adverse events. Such discordant results underscore the need for further exploration of the relationship between error and adverse events. Methods: Patients with operations performed at a single institution and abstracted into the American College of Surgeons National Surgical Quality Improvement Program from January 1, 2018, to December 31, 2018 were examined. This matched case control study comprised cases who experienced a postoperative morbidity or mortality. Controls included patients without morbidity or mortality, matched 2:1 using age (±10 years), sex, and Current Procedural Terminology (CPT) group. Two faculty surgeons independently reviewed records for each case and control patient to identify diagnostic, technical, judgment, medication, system, or omission errors. A conditional multivariable logistic regression model examined the association between error and morbidity. Results: Of 1899 patients, 170 were defined as cases who experienced a morbidity or mortality. The majority of cases (n=93; 55%) had at least 1 error; of the 329 matched control patients, 112 had at least 1 error (34%). Technical errors occurred most often among both cases (40%) and controls (23%). Logistic regression demonstrated a strong independent relationship between error and morbidity (odds ratio=2.67, 95% confidence interval: 1.64–4.35, P <0.001). Conclusion: Errors in surgical care were associated with postoperative morbidity. Reducing errors requires measurement of errors.